Effectiveness of the fourth dose of COVID-19 vaccines against severe COVID-19 among adults 40 years or older in Brazil: a population-based cohort studyResearch in context - Felippe Lazar Neto; Matt D.T. Hitchings; Avnika B. Amin; Giovanny V.A. de França; Margaret L. Lind; Mario Sergio Scaramuzzini Torres; Daniel Henrique Tsuha; Roberto D. de Oliveira; Derek A.T. Cummings; Natalie E. Dean; Jason R. Andrews; Albert I. Ko; et al. (Elsevier, 2024)
Summary: Background: The emergence of COVID-19 variants with immune scape and the waning of primary vaccine schemes effectiveness have prompted many countries to indicate first and second booster COVID-19 vaccine doses to prevent severe COVID-19. However, current available evidence on second booster dose effectiveness are mostly limited to high-income countries, older adults, and mRNA-based vaccination schemes scenarios. We aimed to investigate the relative vaccine effectiveness (rVE) of the fourth dose compared to three doses for severe COVID-19 outcomes in Brazil; and compare the rVE of a fourth dose with an mRNA vaccine compared to adenovirus-based product in the same settings. Methods: We performed a target emulated trial using a population-based cohort of individuals aged 40 years or older who have received a homologous primary scheme of CoronaVac, ChAdOx1, or BNT162b2, and any third dose product and were eligible for the fourth dose in Brazil. The primary outcome was COVID-19 associated hospitalization or death. We built Cohort A matching individuals vaccinated with a fourth dose to individuals who received three doses to estimate the rVE of the fourth dose. We built Cohort B, a subset of Cohort A, matching mRNA-based (mRNA) to adenovirus-based fourth dose vaccinated individuals to compare their relative hazards for severe COVID-19. Findings: 46,693,484 individuals were included in Cohort A and 6,763,016 in Cohort B. 45% of them were aged between 40 and 60 years old, and 48% between 60 and 79 years old. In Cohort A, the most common previous series was a ChAdOx1 two-dose followed by BNT162b2 (44%), and a CoronaVac two-dose followed by a BNT162b2 (36%). Among those fourth dose vaccinated, 36.9% received ChAdOx1, 32.7% Ad26.COV2.S, 25.8% BNT162b2, and 4.7% CoronaVac. In Cohort B, among those who received an adenovirus fourth dose, 53.7% received ChAdOx1 and 46.3% received Ad26.COV2.S. The estimated rVE for the primary outcome of four doses compared to three doses was 44.1% (95% CI 42.3-46.0), with some waning during follow-up (rVE 7-60 days 46.8% [95% CI 44.4-49.1], rVE after 120 days 33.8% [95% CI 18.0-46.6]). Among fourth dose vaccinated individuals, mRNA-based vaccinated individuals had lower hazards for hospitalization or death compared to adenovirus-vaccinated individuals (HR 0.81, 95% CI 0.75-0.87). After 120 days, no difference in hazards between groups was observed (HR 1.35, 95% CI 0.93-1.97). Similar findings were observed for hospitalization and death separately, except no evidence for differences between fourth dose brands for death in Cohort B. Interpretation: In a heterogeneous scenario of primary and first booster vaccination combinations, a fourth dose provided meaningful and durable protection against severe COVID-19 outcomes. Compared to adenovirus-based booster, a fourth dose wild-type mRNA vaccine was associated with immediate lower hazards of hospitalization or death unsustained after 120 days. Funding: None.